A Monitoria na formação do estudante de pedagogia e suas contribuições para a docência - LINS, Gesiely Milena da Silva (2022)
This article seeks to report the experiences of monitoring in higher education in the discipline Special Inclusive Education, highlighting the role of the monitor in the education of the pedagogy student and their contributions to future teaching. The work was structured in two phases: in the first, a bibliographic survey, material records, study sessions; in addition to planning actions in the classrocm. In the second phase, pedagogical practices were carried out in the context of the classroom, such as assisting the teacher in dialogued expository classes, accompanying students in their work, contributing to the elaboration of didactic resources, among others. It is concluded that the Monitoring Project in higher education helps the initial teacher training, considering that it allows the preparation for teaching, expands the construction of knowledge and the skills of the studentmonitor. As well as contributed to the formation of the student in the construction of her professional identity and her future teaching practice.